Influence of toothbrushing on enamel softening and abrasive wear of eroded bovine enamel: An in situ study - Rios, Daniela; Honório, Heitor Marques; Magalhães, Ana Carolina; Buzalaf, Marília Afonso Rabelo; Palma-Dibb, Regina Guenka; De Andrade Moreira Machado, Maria Aparecida; da Silva, Salete Moura Bonifácio (FapUNIFESP (SciELO), 2006)
This study assessed the surface softening and abrasive wear of eroded bovine enamel with or without the influence toothbrushing. Five volunteers took part in this in situ study of 5 days. They wore acrylic palatal appliances containing 6 bovine enamel blocks divided in two rows with 3 blocks, which corresponded to the studied groups: erosion without toothbrushing (GI) and erosion with toothbrushing (GII). The blocks were subjected to erosion by immersion of the appliances in a cola drink for 10 minutes, 4 times a day. After that, no treatment was performed in one row (GI), whereas the other row was brushed (GII). The appliance was then replaced into the mouth. Enamel alterations were determined using profilometry and microhardness tests. Data were tested using paired Student's t test (p < 0.05). The mean wear values (μm) and percentage of superficial microhardness change (%SMHC) were respectively: GI - 2.77 ± 1.21/91.61 ± 3.68 and GII - 3.80 ± 0.91/58.77 ± 11.47. There was a significant difference in wear (p = 0.001) and %SMHC (p = 0.001) between the groups. It was concluded that the wear was more pronounced when associated to toothbrushing abrasion. However, toothbrushing promoted less %SMHC due to the removal of the altered superficial enamel layer.
Keywords: Beverages; Tooth abrasion; Tooth erosion